Cytotoxic effects of damnacanthal and damnacanthal-doxorubicin combination on human breast cancer cell line (MCF-7) - Abdul Aziz, Muhammad Yusran (2012)
Damnacanthal is a biologically active antraquinone derivative isolated from roots of Morinda sp., belonging to the Rubiaceae family. This plant has a long history of use as a food in tropical regions throughout the world. The purpose of this study was to examine the in vitro cytotoxicity effect of damnacanthal and combination of damnacanthal with doxorubicin on human breast carcinoma (MCF-7). MTT assay was used to determine the cytotoxic properties of damnacanthal towards various cancer cell lines, normal cell lines and immune cells. Results showed that damnacanthal displayed strong killing effect towards the cancerous cell lines and moderate effect towards normal cells lines. Among the cancer cell lines, damnacanthal showed strong cytotoxic towards MCF-7 cells with CD50 8.2 ± 0.7 μg/mL after 72 hours treatment period. In contrast, no cytotoxicity was detected in primary mouse splenocytes, mouse thymocytes and mouse bone marrow. In particular, damnacanthal showed cytotoxicity in a dose- and time-dependent manner in the MTT assay. Thus, MCF-7 cells were used to determine the mode of cell death with damnacanthal alone and combination with doxorubicin. In the cell viability assay, the percentage viability of MCF-7 cells is lower when the cells are treated with combination of damnacanthal and doxorubicin than doxorubicin alone. In the cell cycle with flow cytometry analysis, damnacanthal arrested the cell cycle of MCF-7 cells at G1 phase and doxorubicin arrested at G2/M phase. The percentage population of MCF-7 cells enter sub G0 phase are increased when the cells were treated with combination of damnacanthal and doxorubicin. The mode of cell death was mainly apoptosis by acridine orange/propidium iodide (AO/PI) dual staining method and Annexin V-FITC/PI assays. Gross morphology of treated cells observed through AO/PI showed the presence of blebbings cells, chromatin condensation and DNA fragmentation, indicating apoptosis. Annexin V-FITC/PI staining showed that substantial early apoptotic cells were detected in MCF-7 cells treated with damncanthal alone and in combination with doxorubicin. The changes of percentage intracellular proteins were analyzed using flow cytometer. The percentage of Bcl-2 protein is higher than p53 protein in the control group. While in the treatment group, the percentage of Bcl-2 protein decreased significantly and p53 protein increased significantly. The changes of expression level of apoptotic related genes caused by damnacanthal and doxorubicin were profiled using multiplex gene expression profiler (GeXP). The expression levels of genes that give significant signal were not much different at 12 and 24 hours. Out of 15 genes that were analyzed, four genes showed detection in expression level; BAX, p21, caspase-3 and caspase-7. The expression of these pro-apoptotic genes is up-regulated in the treated group compared to control. Among the treated group, the combination treatment of damnacanthal and doxorubicin showed higher expression level of these pro-apoptotic genes. The findings in the intracellular protein detection and changes in the expression level of apoptotic related genes reflect that the mechanism of damnacanthal induced apoptosis in the human breast cancer cells was by the intrinsic and caspases induction pathway. In conclusion, damnacanthal is more toxic towards cancer cell lines rather than normal cell lines and primary cells and showed the potential use as a promising agent for apoptosis induction alone and/or with combination with doxorubicin. The induction of apoptosis involved important proapoptotic genes which are BAX, p53, p51 caspase-3 and caspase-7.